La dislexia y su incidencia en el aprendizaje en los estudiantes de 4to EGB, Escuela 5 de Junio, El Empalme, 2022 - Del Valle Moreira, Vanessa Anunciata (2023)
Dyslexia negatively affects the reading process and academic performance of fourth-grade students in General Basic Education. The purpose of this project is to strengthen educational quality by providing training to teachers and legal representatives, who are also parents, in order to improve students' academic performance through the design of a Methodological Guide for the Educational Community. The difficulties children face in key areas such as reading and writing, which are foundational to the teaching process, lead to low self-esteem and isolation, resulting in insecure and introverted children. Reading and writing skills are present in all areas of learning and are crucial for successful education, enabling children to feel competent in different situations and settings. However, when they do not master these core actions in the teaching-learning process, it creates isolation and insecurity in them. Students experiencing difficulties in reading and writing can be supported by timely assistance from teachers, parents, and, if necessary, a professional in Psychopedagogy. The content of this educational project is divided into five chapters, each containing scientific, bibliographic, and field information related to the research topic. A cultural and social perspective is important to fully understand the significance of the reading process in students' teaching and learning.